Formulasi Pembelajaran PAI dan Implikasi Terhadap Motivasi Belajar Peserta Didik di SMA Negeri 10 Enrekang - St. Wardah Hanafie Das; Muh. Syakir; Juliadi Juliadi (Al-Ishlah: Jurnal Pendidikan Islam, 2019)
Public schools such as Enrekang 10 Public High Schools need effective and massive character education and Islamic Education (PAI). The 2013 curriculum emphasizes PAI as a core subject in shaping the character of students at school. Students at the high school level are in the adolescent period which is still mentally unstable. Students at the high school level are in the adolescent period which is still mentally unstable. This period students (Muslims) need PAI in guarding psychological development. Reality at Enrekang 10 High School, students lacked focus on learning PAI due to various variables surrounding it. On the other hand, the characteristics of PAI are complex, namely doctrine, belief, knowledge, practice, and moral behavior. Various problems that were born in PAI learning, both from the material aspects in the 2013 curriculum, students' learning motivation, educator competencies, and other aspects. The 2013 curriculum in the field of PAI should be adaptive and summarize the psychological development of students and relevant to social reality. PAI educators are required to have multi-competencies, namely pedagogical, professional, personality, social, religious, cybernetics, entrepreneurship, and managerial competencies. PAI educators 'competencies are considered more likely to increase students' learning motivation. Competence of PAI educators can master learning tools, procedures, systematics, media design and learning resources, setting learning strategies and methods, learning evaluation design, and classroom management